Analysis of the collective agreement of the aeronaut’s union between 2019 and 2021 and the critical theory of law - de Oliveira, Paulo Eduardo Vieira; Mendonça, Camila Carvalho (Seven Editora, 2023)
This article aims to comprehend how the syndicate of aeronauts acted during the period of the Covid-19 pandemic in order to guarantee the fundamental rights of workers under the aspect of Critical Theory. For this, bibliographical research was used in scientific articles, books and websites, using the analytical method. In the end, it could be concluded that the Covid-19 pandemic had an impact on labor relations and civil aviation was one of the most affected sectors, nonetheless, under the critical eye of Critical Theory, the syndicate was active to guarantee the rights presented in the convention collective agreement of 2019/2020 in the collective agreement 2020/2021, but it was necessary to carry out collective agreements with salary reduction or unpaid leave aiming to guarantee employment.DOI:https://doi.org/10.56238/uniknowindevolp-121